Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Pelanggan Terhadap Pembelian Tiket Pesawat Secara Online di Situs Air Asia - Algusri, Jeki (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2019)
This study aims to identify the factors that affect customers, especially in the city of Padang in making airline ticket purchase decisions online on the AirAsia website. The factors that influence this purchasing decision are explained by several variables: intelligence, design, choice, cost-saving, time-saving, and satisfaction. This research is a quantitative descriptive study using SPSS 16. This research was conducted through a survey of 101 respondents who purchased airline tickets online on the AirAsia website. The results of this study show that intelligence, design choice, cost-saving and time-saving have a positive effect on satisfaction in purchasing decisions. From these results, it can be concluded that the factors that influence purchasing decisions, namely intelligence, design, choice, cost-saving and time-saving have a positive effect on satisfaction.